Artificial intelligence approaches in student modeling: half decade review (2010-2015) - Sani, Salisu Muhammad; Bichi, Abdullahi Baffa; Ayuba, Shehu (D-LAR Labs (Digital Library of Academic Research), 2016)
Intelligent Tutoring Systems (ITSs) are special classes of E-learning systems designed using Artificial Intelligence (AI) approaches to provide adaptive and personalized tutoring based on the individuality of students. The student model is an important component of an ITS that provides the base for this personalization. During the course of interaction between student and the ITS, the system observe student’s actions and other behavioral properties, create a quantitative representation of these student’s attributes called a student model.